GRAMÁTICA: O DISCURSO INDIRETO NUMA PERSPECTIVA DISCURSIVA - Bianchi, Mariluci (Organon, 2003)
According Authier-Revuz, the speech functions of the reportedspeech are identified and analysed as one of the forms of related speech,that a the place of the Other in the through. There fore, the function of thereported speech exceed the ones defined by traditional grammar. Throughthe enunciations, objectify to demonstrate that the speech cited should beidentify as report of enunciation acts and nor simply with words, as proclaimthe traditional grammar. These insertions of speech-others presupposea position that preside the choice: mention themselves the others forsome reason, that can be in concordance, to be stand opponent the placement,for writing and/or to reinforce the position and obtain a possibleeffect of sense.